Antioxidant capacity of alcoholic beverages based on infusions from non-traditional spicy-aromatic vegetable raw materials - Kuzmin, Oleg; Kucherenko, Volodymyr; Sylka, Iryna; Isaienko, Volodymyr; Furmanova, Yuliia; Pavliuchenko, Olena; Hubenia, Vyacheslav (My University, 2020)
Antioxidant ability of infusions of spicy-aromatic plants: Perilla frutescens; Elsholtzia stauntonii Benth; Artemisia abrotanum; Monarda didyma; Agastache foeniculum; Satureja hortensis; Ruta graveolens; Nepeta transcaucasica Grossch was determined by redoxmetry and pHmetry; sensory evaluation – by expert method; the results of mathematical and statistical processing – by the method of linear Pearson correlation. Results and discussion. The minimum theoretical value of redox potential (RP) for plant aqueous-alcoholic infusions was obtained, which has a value from 228.0 mV (Satureja hortensis) to 260.4 mV (Agastache foeniculum). The actual measured RP of infusions was established – from 117 mV (Elsholtzia stauntonii Benth) to 134 mV (Nepeta transcaucasica Grossch). The hydrogen index for aqueous-alcoholic infusions from spicy-aromatic raw materials has a value of 6.66 units pH (Agastache foeniculum) to 7.20 units pH (Satureja hortensis). Aqueous-alcoholic infusions from vegetable raw materials and a volume fraction of ethanol of 40% have the value of recovery energy (RE) in the range from 100.0 mV (Nepeta transcaucasica Grossch) to 138.2 mV (Ruta graveolens). Aqueous-alcoholic infusions from spicy-aromatic raw materials have values of sensory evaluation (S.e.) from 9.50 to 9.69 points. The highest value of S.e. 9.69 points is characteristic of Nepeta transcaucasica Grossch: color – light brown; taste – mint; aroma – soft, pleasant, sweet. Conclusion. It is proposed for the technology of alcoholic beverages the use of aqueous-alcoholic infusions from Ruta Gravelens and Nepeta transcaucasica Grossch, which received increased antioxidant characteristics RE 138.2 mV and RE 100.0 mV, respectively, and positive S.e. 9.57 and S.e. 9.69 points on a 10-point scale.Антиоксидантну здатність настоїв з пряно-ароматичних рослин: Perilla frutescens; Elsholtzia stauntonii Benth; Artemisia abrotanum; Monarda didyma; Agastache foeniculum; Satureja hortensis; Ruta graveolens; Nepeta transcaucasica Grossch визначали за методом редоксметрії та рН-метрії; сенсорні показники – за експертним методом; результати математико-статистичної обробки – за методом лінійної кореляції Пірсона. Результати. Отримано мінімальне теоретичне значення окисно-відновного потенціалу для рослинних водно-спиртових настоїв, яке змінюється від 228.0 мВ (Satureja hortensis) до 260.4 мВ (Agastache foeniculum). Встановлено фактичний виміряний окисно-відновний потенціал настоїв – від 117.0 мВ (Elsholtzia stauntonii Benth) до 134.0 мВ (Nepeta transcaucasica Grossch). Водневий показник для водно-спиртових настоїв з пряно-ароматичної сировини має значення від 6.66 од. рН (Agastache foeniculum) до 7.20 од. рН (Satureja hortensis). Водно-спиртові настої з рослинної сировини та об’ємною часткою етанолу 40% мають величину енергії відновлення (ЕВ) в межах від 100.0 мВ (Nepeta transcaucasica Grossch) до 138.2 мВ (Ruta graveolens). Водно-спиртові настої з пряно-ароматичної сировини мають значення сенсорних показників (S.e.) від 9.50 до 9.69 балів. Найбільше значення S.e. – 9,69 балів характерне для Nepeta transcaucasica Grossch: колір – світло-коричневий; смак – м'ятний; аромат – м'який, приємний, солодкуватий Висновки. Запропоновано для технології алкогольних напоїв застосування водноспиртових настоїв з Ruta graveolens та Nepeta transcaucasica Grossch, які отримали підвищені антиоксидантні характеристики ЕВ – 138.2 мВ та ЕВ – 100.0 мВ відповідно, та позитивні сенсорні показники S.e. – 9.57 та S.e. – 9.69 балів за 10-бальною шкалою.
Keywords: spicy-aromatic; antioxidant; redox; alcohol; пряно-ароматичний; infusion; окисно-відновний потенціал; антиоксидант; настій; алкоголь; кафедра технології ресторанної і аюрведичної продукції